L'autunno del Metastasio: gli ultimi drammi per musica di Johann Adolf Hasse - Mellace, Raffaele 1969- (Florence Olschki, 2007)
The book illustrates the last decade (1760-1771) in the production of Metastasio and Hasse: five dramas and three theatrical festivals commissioned by the imperial court and the courts of Saxony and Poland.
Includes bibliographical references and index.
Keywords: Hasse, Johann Adolf -- 1699-1783; Metastasio, Pietro -- 1698-1782; Opera; Libretto